The influence of perceived usefulness, percieved ease of use and awareness of services on consumers intention to use e-money mobile - Khatimah, Husnil; Halim, Fairol (AENSI, 2014)
This research examines consumers’ intention to use e-money mobile that adapted from two prior variables of the TAM (Technology Acceptance Model).This study introduce additional variable that is awareness of service.The conceptual framework of e-money mobile is reviewed to understand behavioral intention of consumers from perceived usefulness, perceived ease of use, perceived behavioral control and awareness of service. Quantitative method is utilized as sources of data collection.A total of one thousand respondents are selected using stratified sampling method in Padang, Indonesia. Descriptive analysis and Multiple Regression analysis are conducted to analyze the data.The article ended with suggestion for future studies.